Sliding Mode-Based Control of a UAV Quadrotor for Suppressing the Cable-Suspended Payload Vibration - Tom Kusznir; Jaroslaw Smoczek (Journal of Control Science and Engineering)
This paper addresses the problem of damping vibrations of a cable-suspended payload during positioning of the quadrotor. A nonlinear model is derived for the coupled quadrotor-pendulum system in the X-Z plane using Euler–Lagrange formulation. Sliding mode control (SMC) is used for horizontal positioning and payload vibration damping, while a feedback linearizing controller is used for both altitude and attitude control. The SMC surface parameters are determined by placing the eigenvalues of the linearized system at a desired position. The simulation results show the effectiveness of the proposed control method in minimizing payload vibration by comparing it with a partial feedback linearizing controller and a ZVDD input shaper.